IMPLEMENTASI INTRAKURIKULER PENGEMBANGAN DIRI UNTUK MENINGKATKAN SOFTSKILL PESERTA DIDIK DI MAS ULUL ABSHAR - Mia Siti Nurazizah; Sutendi, Muhammad; Fitriani, N. Rida; Romadon, Khoeru; Winda (Institut Nahdlatul Ulama Tasikmalaya, 2025)
This study examines the implementation of intracurricular self-development activities, specifically sewing and agriculture, as an effort to enhance students' soft skills at MAS Ulul Abshar, Cianjur, in response to the demand for graduates who are not only academically intelligent but also possess strong non-academic abilities. This study used descriptive qualitative methods, data were collected through interviews, observations, and documentation. The findings indicate that these two activities are innovations aligned with the madrasah's vision and mission to produce independent, capable, and skilled graduates. These intracurricular activities serve as an effective means of instilling practical and soft skills values ​​, such as responsibility, independence, and entrepreneurship, which have proven to provide graduates with functional provisions in the real world of work, including working in a garment factory or starting a business based on agricultural and sewing products.